PROFILE OF ADOLESCENT BRIGHTS AND IMPLICATIONS FOR GUIDANCE AND COUNSELING (Descriptive Study on Students of SMKN 2 Kota Serang Teaching 2022/2023) - Muhammad Yusuf Haqqi; Rochani; Deasy Yunika Khairun (Cakrawala Pedagogik, 2022)
This study aims to reveal the profile of brawls between students, their impact and it’s implications for guidance and counseling services at SMKN 2 Serang City. The type of this research is a descriptive quantitative. The subjects of this study were 793 students at grade IX. The sampling technique used in this study was random sampling, so 71 students were taken randomly for sampling. By realibility value 0,98. . The data obtained were analyzed by using product moment analysis techniques. The data obtained were analyzed using product moment analysis techniques. The results of the study indicate that brawling behavior, apart from violating social norms, can also endanger oneself and others, and can damage public facilities. This can be seen from the total response achievements of respondents who are in the number between 60-90 with a fairly good to very good category.